LncRNA-mRNA integrated networks in the neuroendocrine system of bisphenol a-treated mice induce cellular dysfunctions by disrupting transcriptional homeostasis - Oh, Seung-Mi (2025)
Bisphenol A (BPA) is a widely used xenoestrogen that can disrupt neuroendocrine and immune regulation through multiple hormone receptors. This study investigated BPAinduced long non-coding RNA (lncRNA)-mRNA interactions in the cerebral cortex and hypothalamic-pituitary-thyroid (HPT) axis of adult male mice. Transcriptome sequencing and comprehensive lncRNA annotation identified 14,858 novel lncRNA transcripts. Integrated network analysis using weighted gene co-expression network analysis (WGCNA) revealed four distinct tissue-specific modules: neuronal signaling alterations (Tac1, Htr1b, Npy), RNA splicing modifications (Srsf5), PI3K/Akt-mediated cellular dysfunction (Creb5, Cdkn1a), and immune receptor signaling disruptions (Trbv15, Fcrla). These findings suggest that BPA reprograms transcriptional networks in a tissue-specific manner, potentially disrupting hormone-related neurotransmission, metabolic regulation, and immune signaling via lncRNA-mediated mechanisms. Such systems-level reprogramming of the immune-neuroendocrine network (INEN) provides novel mechanistic insights and biomarker candidates for assessing and mitigating the health impacts of environmental endocrine disruptors.